On-line-off-line convergence strategies of the Cacau Show for engaging your consumers (Revista Brasileira de Contabilidade e Gestão, 2021)
The objective of this study is to understand the on-line-off-line convergence strategies used by the Cacau Show brand to attract consumers. The methodology used was a qualitative and descriptive research, a case study, with off-lineobservation of the brand stores in Vale dos Sinos/RS and Mega Store in Porto Alegre and on-line observation with of the brand's social networks. As main results, it is stated that Cacau Show uses on-line-off-line convergence to connect webrooming and showrooming channels, creating interaction and engagement with consumers, with integration of information and marketing mix.
Keywords: Engagement Marketing; On-Line-Off-Line Convergence; Marketing Mix; Webrooming; Showrooming